Enhanced Photocatalytic Hydrogen Production on Cd-, Te-, Se-, and S-Doped Titanium Dioxide Catalysts - Kaya, Sefika; Saka, Ceren; Çağlar, Aykut; Kaya, Mustafa; Kivrak, Hilal; Çağlar, Aykut (Springer, 2023)
Herein, cadmium (Cd)-, tellurium (Te)-, selenium (Se)-, and sulfur (S)-doped titanium dioxide (TiO2) support material catalysts are prepared via incipient wetness impregnation. Hydrogen generation performances of the prepared catalysts from sodium borohydride (NaBH4) by methanolysis are investigated. Experimental studies are carried out under ultraviolet (UV) illumination and in the dark. The highest initial hydrogen generation rate is reached on 0.1% Cd/TiO2 catalyst under UV illumination. The optimum catalyst, sodium borohydride, and methanol amounts and temperature parameters affecting the initial hydrogen generation rate are investigated and obtained as 0.025 g, 0.150 g, 2 mL, and 60 degrees C, respectively. The initial hydrogen generation rate of 0.1% Cd/TiO2 catalyst is 16130.64 mL/min.gcat in optimum conditions. The activation energy of the reaction with the 0.1% Cd/TiO2 catalyst is calculated by carrying out kinetic studies. The activation energy is 22.48 kJ/mol. X-ray diffraction (XRD), electron microscopy with energy-dispersive x-ray spectroscopy (SEM-EDX), inductively coupled plasma mass spectrometry (ICP-MS), x-ray photoelectron spectroscopy (XPS), and transmission electron microscopy (TEM) analytical techniques are performed to characterize the catalysts. The results show that TiO2 catalysts doped with Cd, Te, Se, and S, which are cheaper than noble metals, are promising for the production of hydrogen from NaBH4 by methanolysis under UV illumination.
Keywords: Hydrogen; Methanolysis; Sodium Borohydride; Catalyst; Titanium Dioxide